Chemerin regulates formation and function of brown adipose tissue: Ablation results in increased insulin resistance with high fat challenge and aging. Issue 7 (5th June 2021) - Zhang, Yiqiang; Shen, Wen‐Jun; Qiu, Shuo; Yang, Pinglin; Dempsey, Garrett; Zhao, Lei; Zhou, Qin; Hao, Xiao; Dong, Dachuan; Stahl, Andreas; Kraemer, Fredric B.; Leung, Lawrence L.; et al.
Abstract: Apart from its role in inflammation and immunity, chemerin is also involved in white adipocyte biology. To study the role of chemerin in adipocyte metabolism, we examined the function of chemerin in brown adipose tissue. Brown and white adipocyte precursors were differentiated into adipocytes in the presence of Chemerin siRNA. Chemerin‐deficient ( Chem −/− ) mice were compared to wild‐type mice when fed a high‐fat diet. Chemerin is expressed during brown adipocyte differentiation and knock down of chemerin mRNA results in decreased brown adipocyte differentiation with reduced fatty acid uptake in brown adipocytes. Chem −/− mice are leaner than wild‐type mice but gain more weight when challenged with high‐fat diet feeding, resulting in a larger increase in fat deposition. Chem −/− mice develop insulin resistance when on a high‐fat diet or due to age. Brown adipose depots in Chem −/− mice weigh more than in wild‐type mice, but with decreased mitochondrial content and function. Compared to wild‐type mice, male Chem −/− mice have decreased oxygen consumption, CO2 production, energy expenditure, and a lower respiratory exchange ratio. Additionally, body temperature of Chem −/− mice is lower than that of wild‐type mice. These results revealed that chemerin is expressed during brown adipocyte differentiation and has a pivotal role in energy metabolism through brown adipose tissue thermogenesis.